Distal phalanges of Eosimias and Hoanghonius. Issue 86 (September 2015) - Gebo, Daniel L.; Beard, K. Christopher; Ni, Xijun; Dagosto, Marian
Abstract: Seven primate distal phalanges have been identified from two middle Eocene fossil localities (Locality 1 and Nanbaotou) in the Yuanqu Basin, China, providing the first evidence of distal phalangeal morphology in Asian Eocene adapiform and eosimiid primates. The bones are best allocated to the basal anthropoid Eosimias centennicus and to hoanghoniine adapiforms. All distal phalangeal specimens display a morphology consistent with nail-bearing fingers and toes. The hallucal distal phalanx of the basal anthropoid Eosimias is more similar to that of primitive tarsiiforms than to crown group anthropoids. The adapiform distal phalanges from Locality 1 are allocated to Hoanghonius stehlini while those from Nanbaotou are tentatively assigned to an indeterminate hoanghoniine because dental remains of adapiforms have yet to be identified from this site. The distal phalangeal anatomy of hoanghoniines differs slightly from that documented for adapines and notharctines. One distal phalanx from Locality 1 shows a second pedal digit "grooming claw" morphology as noted for notharctines by Maiolino et al. (2012) and cercamoniines by Von Koenigswald et al. (2012).